2005
DOI: 10.1159/000086317
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Japanese Patients with Obsessive-Compulsive Disorder – Effectiveness of Behavior Therapy and Fluvoxamine

Abstract: Background: The aim of this study was to confirm and compare the efficacy of fluvoxamine (the only licensed SSRI for treatment for OCD in Japan) and behavior therapy in treating Japanese patients with OCD. In addition, we investigated predictors of these treatments. Methods: Thirty-one outpatients meeting the DSM-III-R criteria for OCD without any axis I disorder were randomly assigned to one of three treatment conditions: BT (behavior therapy ± pill placebo), FLV [autogenic training (a psychological placebo f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 52 publications
4
44
0
Order By: Relevance
“…One study compared CBT9pill placebo, autogenic training (a psychological placebo for OCD)9fluvoxamine and autogenic training9pill placebo. Patients in the CBT group had the highest improvement scores, followed by fluvoxamine, which was still significantly superior to placebo (Nakatani et al 2005).…”
Section: )(E)mentioning
confidence: 84%
See 1 more Smart Citation
“…One study compared CBT9pill placebo, autogenic training (a psychological placebo for OCD)9fluvoxamine and autogenic training9pill placebo. Patients in the CBT group had the highest improvement scores, followed by fluvoxamine, which was still significantly superior to placebo (Nakatani et al 2005).…”
Section: )(E)mentioning
confidence: 84%
“…The proportion of patients that relapsed was statistically significantly higher in the placebo group (Fineberg et al 2007) (A). Á Fluvoxamine was and found to be superior to placebo in DBPC studies (Goodman et al 1989b(Goodman et al , 1996Hohagen et al 1998;Nakatani et al 2005) and in clomipramine-controlled trials (Milanfranchi et al 1997;Mundo et al 2000). The slow-release form was also superior to placebo (Hollander et al 2003c).…”
Section: Selective Serotonin Reuptake Inhibitors (Ssris)mentioning
confidence: 99%
“…Although behaviour therapy and selective serotonin reuptake inhibitors are considered the most popular treatment options for OCD, a recent study found behaviour therapy much more effective than medication [2]. In terms of psychotherapy, cognitive behaviour therapy (CBT) for general anxiety disorders was found superior to other psychological therapies [3].…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence has accumulated to underpin the efficacy of ERP, which has become the preferred psychological treatment for OCD [3,4,5]. However, ERP is not entirely problem-free.…”
Section: Introductionmentioning
confidence: 99%